2012
DOI: 10.1097/01.sa.0000414262.66707.e2
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Epidural Analgesia and Acute Pain Management

Abstract: The 145 recruited patients undergoing elective orthopedic lower-limb surgery had 1 of the following: body mass index greater than 35 kg/m 2 and poorly palpable or impalpable spinous processes, moderate to severe lumbar scoliosis, or previous lumbar spinal surgery. Patients were randomized to receive spinal anesthesia by the conventional surface landmarkYguided technique (group LM) or by ultrasound-guided technique (group US). The study procedures were performed 30 to 45 minutes before surgery. For patients in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 0 publications
4
53
0
4
Order By: Relevance
“…Due to the small number of patients receiving epidural analgesia in our cohort, we were not able to analyse if its use and its opioid-sparing effect facilitated earlier postoperative extubation, although the benefits of epidural analgesia have been shown in other surgeries and the opioid-sparing effects of regional anaesthesia is an outcome of interest. (15) Our experience was drawn over a period of 16 years, during which surgical and anaesthesia techniques have improved. It is thus likely that a patient presenting for CRS and HIPEC today will benefit from our learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the small number of patients receiving epidural analgesia in our cohort, we were not able to analyse if its use and its opioid-sparing effect facilitated earlier postoperative extubation, although the benefits of epidural analgesia have been shown in other surgeries and the opioid-sparing effects of regional anaesthesia is an outcome of interest. (15) Our experience was drawn over a period of 16 years, during which surgical and anaesthesia techniques have improved. It is thus likely that a patient presenting for CRS and HIPEC today will benefit from our learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…041/001; www.awmf.de) [32]. For open procedures, TEA is indicated for middle and major thoracic surgery and should, assuming no contraindications, be initiated preoperatively at thoracic segments Th4-Th7 [33]. A prospective, randomized, clinical trial showed a lower rate of postoperative pulmonary complications (6.6 vs. 35%) in 60 thoracic surgery patients using a 'fast-track' concept with TEA compared with conventional management [34].…”
Section: Thoracic Epidural or Paravertebral Analgesiamentioning
confidence: 97%
“…Thoracic epidural analgesia (TEA) is a regional anesthesia‐based technique used to relieve thoracic pain after surgery or during critical care in small animals and humans (Wetmore & Glowaski ; Hansen ; Manion & Brennan ). Concern that TEA may induce side effects potentially unsafe for the patient has delayed acceptance of the technique into routine use.…”
Section: Introductionmentioning
confidence: 99%